Basic Principles of Sports School in Working with the Early Primary School Children - Nenad M. Sinđelić (University of Belgrade, Teacher Education Faculty, 2020)
The aim of this paper is to explore and analyze, by using the school of football as a model, the operational principles on which sports schools are based and to determine their possible implications for physical education classes in the lower grades of primary school. The pedagogical literature emphasizes the importance of sports for the formation of healthy and versatile children and young people with desirable psychological and social competences who will be able to fulfill, by developing and manifesting creative and human potentials, their biological, social and psychological needs for playing and socializing. In this regard, the lack of engagement of some schools/primary school teachers, or the society as a whole, in the extracurricular activities of the lower primary school pupils is critically interpreted, as well as the lack of systematic assistance and support for overcoming this situation. In response, the number of sports schools attended by a large percentage of pupils aged 7-11 is on the rise. Bearing in mind that sport is very important for building a child's personality, the question of the quality of the pedagogical work of sports schools with young children of primary school age is gaining momentum.